Russia’s Soft Power as a Limited Efficiency Tool in Lithuania - Česnakas, Giedrius; Isoda, Vytautas (Politologija, 2019)
[full article, abstract in English; abstract in Lithuanian] Lithuania has been a target of Russia’s soft power efforts for the past two decades. The aim of this article is to analyse Russia’s soft power influence possibilities in Lithuania. First, it analyzes how soft power is interpreted in Russia compared to the Western conception. Then, Russia’s soft power instruments and their core goals are reviewed, not all of which fall under the category of “soft power instruments” according to the Western understanding. The article proceeds with demographic changes in Lithuania and trends of consumption of Russian culture and information in Lithuania. The main argument is that Russia is not aiming to apply soft power to the general Lithuanian society but to particular groups within the population (Russophone minorities and residents with sentiments for the Soviet Union). It can be assumed that demographic trends and Russia’s aggressive actions will increasingly limit its soft power capabilities. However, the greatest setback to Russia’s soft power in Lithuania is arguably caused by its continuing reliance on hard power when it comes to countries of the post-Soviet space.